Don’t Fear the Reaper? The Zombie University and Eating Braaaains - Tara Brabazon (KOME: An International Journal of Pure Communication Inquiry, 2016)
This article explores the role and function of neoliberalism in higher education, particularly in its manifestations after the Global Financial Crisis. Theories of managerialism are overlaid not only with questions about the purpose and role of higher education in the economy, but also the renegotiation of power and identity after 2008. Ulrich Beck’s zombie concept is reactivated and applied to the university. The paper moves through a discussion of the zombie and Beck’s zombie categories and concepts, and then concludes with a section applying these ideas to higher education.